2022
DOI: 10.1080/10282580.2022.2044802
|View full text |Cite
|
Sign up to set email alerts
|

‘Spaces’ for restorative development: international case studies on restorative services

Abstract: This paper examines the concept of the 'spaces' into which restorative services develop (Vaandering 2014;Braithwaite, 2016;Maglione, 2019;Hobson et al, 2021). We conceptualise such 'spaces' as: social, the people and communities; as political, the will for developments; as physical, the geography and facilities; and as economic, dependent on the resources available. The first case study examines the hub-and-spoke model from Gloucestershire, England, where a top-down approach with buy-in at the statutory level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Distinctive roles and UPA provides a useful focus to examine local development initiatives. The limited studies of the challenges faced by youth in Sierra Leone have noted a legacy of historical neglect, social marginalisation and exclusion of youth by successive governments (Bangura, 2016;Hobson et al, 2022). This research suggests the need for authorities to closely attend to youth issues in order to ensure continuing stability and prevent a relapse into violence when the grievances and frustrations of youth are left unaddressed.…”
Section: Key Findings From the Data Collectionmentioning
confidence: 94%
“…Distinctive roles and UPA provides a useful focus to examine local development initiatives. The limited studies of the challenges faced by youth in Sierra Leone have noted a legacy of historical neglect, social marginalisation and exclusion of youth by successive governments (Bangura, 2016;Hobson et al, 2022). This research suggests the need for authorities to closely attend to youth issues in order to ensure continuing stability and prevent a relapse into violence when the grievances and frustrations of youth are left unaddressed.…”
Section: Key Findings From the Data Collectionmentioning
confidence: 94%
“…We consider the findings under three themes that relate to the ways in which bottom-up and top-down approaches develop and function: cross-sector working, funding and resourcing, and expanding the remit of restorative practices. We provide evidence that demonstrates the benefits in both approaches, and importantly that each approach is often a response to the underlying social and political conditions, and to the 'spaces' for restorative development (Hobson et al, 2022) that are available. We also highlight some of the tensions in the continued development of restorative services and their integration into government policy, including concerns over the undermining of restorative justices' transformative potential, and concerns over the 'dilution' of restorative ideology as provisions increasingly reflect the priorities of their host services and agencies.…”
Section: Introductionmentioning
confidence: 99%
“…There are those who caution that such integration may lead to a new era of professionalisation that appears remote to victims and prevents genuine community participation (Hoyle and Rosenblatt 2016;Wood and Suzuki, 2016;Aertsen, 2006;Gavrielides, 2015). In this way, new restorative services can encounter a broad range of issues and impediments to their development and sustainability, no matter if they are developed from the bottom-up, as community-led schemes, or are constructed from the top-down, as institutionally or organisationally-led programmes (Hobson et al, 2022). In this paper, we seek to add knowledge on the challenges faced by new services and suggests a range of approaches that can be taken to increase the viability and success of new restorative schemes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an evaluation of the Mending Bridges program in New England found that the program has the potential to change behaviors and relationships, impacting the prison community as a whole [5]. Similarly, restorative justice programs have been found to fill various "spaces" in society, such as addressing community distrust of the state in Belfast, Northern Ireland, or providing urban farming schemes for youth in Kenema Town, Sierra Leone [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence on their effectiveness is not entirely consistent, and the impact of restorative justice programs can vary depending on a variety of factors. In addition, restorative justice programs can have transformative effects on individuals and communities, addressing various social, political, physical, and economic "spaces" within society [6].…”
Section: Introductionmentioning
confidence: 99%